Michael Glykas and the Afterlife in Twelfth-Century Byzantium - Papadogiannakis, Yannis (Studies in church history, 2009)
From the range of sources on Byzantine religious life, and Byzantine views on the afterlife in particular, the correspondence of Michael Glykas stands out as precious but neglected evidence. Glykas’s correspondence with people from all walks of life and his engagement with their preoccupations and with other controversial issues of the day reflect a dense network of communication and links with monks, laymen, members of the imperial family and imperial bureaucrats, situating him at the heart of the moral universe of twelfth-century Byzantine culture. Glykas’s correspondence and, in particular, his collection of ‘Questions and Answers’ (Kephalaia) shed light on the kinds of religious issues that were being raised in twelfth-century Byzantium, and they also highlight the multifarious issues and pastoral challenges which Christian theologians had to be prepared to deal with in their pastoral, pedagogical work.